The dynamics of IAA activity and content in leaves and shoot apical meristem (SAM) of isogenic by E genes soybean lines during photoperiodic induction. - Юхно, Ю. Ю.; Жмурко, В. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The dynamics of IAA content and activity in the leaves and shoot apical meristem (SAM) of soybean E genes isogenic lines in the conditions of different day length have been studied. It has been educed that the short-day (SD) lines showed the growing content of IAA in the leaves, and particularly in SAM under long day (16 hour). The IAA dynamics had inverse character under short day (9 hour). The photoperiodic insensitive (PPI) lines showed the growing content of IAA in the leaves, and particularly in SAM, both short and long day approximately equal. SD plants accelerated the transition to flowering under short photoperiod. Flowering rate of PPI plants wasn’t altered under any photoperiodic conditions. Photoperiodic sensitivity of soybean isolines is defined by different states of E genes (dominant and/or recessive). Probably E genes affect the transition to flowering soybean under different photoperiod through their participation in the regulation of activity, content and distribution of plant hormones, such as IAA.